2008
DOI: 10.1111/j.1365-2982.2008.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tolterodine on gastrointestinal transit and bowel habits in healthy subjects

Abstract: Clinical trials and observations suggest that constipation is an uncommon side effect of treating overactive bladder with the muscarinic receptor antagonist tolterodine. Because muscarinic antagonism inhibits gastrointestinal motor activity, we evaluated the effects of tolterodine on bowel habits, gastrointestinal and colonic transit in healthy subjects. In this double-blind study, 36 healthy subjects were randomized to tolterodine extended release (ER, 4 mg daily) or placebo for 6 days. Gastric emptying (GE),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
1
16
1
Order By: Relevance
“…If confirmed in prospective studies of transit and simultaneous symptom measurement, this may lead to better designed treatments that inhibit postprandial responses such as 5-HT 3 antagonists (7,47) and selective muscarinic antagonists (26,27). …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…If confirmed in prospective studies of transit and simultaneous symptom measurement, this may lead to better designed treatments that inhibit postprandial responses such as 5-HT 3 antagonists (7,47) and selective muscarinic antagonists (26,27). …”
Section: Discussionmentioning
confidence: 91%
“…The cholinergic mechanisms involved in increased ileocecal transit have been investigated in a canine model of the ileocolonic region in vivo, with evidence for involvement of muscarinic M 1 and M 3 mechanisms (26,27). If symptoms are aggravated postprandially in IBS, these data suggest that further studies of selective antimuscarinic agents in patients with IBS are indicated.…”
Section: Discussionmentioning
confidence: 99%
“…GE was assessed by scintigraphy using a 300-kcal mixed meal containing 99m Tc-sulfur colloid labeled eggs in all patients [6]. For our laboratory, normal values for GE are 11–39% at 1 hr, 40–76% at 2 hr, and 84–98% at 4 hr.…”
Section: Methodsmentioning
confidence: 99%
“…Obesity is a risk factor for diarrhea [14] and accelerated colonic transit [15]. Besides predisposing to acute leakage by virtue of higher viscus (bladder or rectal) pressure, it is suggested that a higher intra-abdominal pressure may damage the pelvic floor in obese people [9].…”
mentioning
confidence: 99%